Pengaruh Harga Internasional, Ekspor, Harga Tbs, Dan Volume Produksi Biodiesel Terhadap Harga CPO Domestik - Gusti A Gultom; Bayu Krisnamurthi; Bungaran Saragih (Forum Agribisnis, 2023)
The palm oil industry downstream program supports the development of new energy made from palm oil, namely biodiesel. Biodiesel is used as a blend for fuels such as diesel. One of the goals of developing the biodiesel industry is to produce new renewable energy sources so that it can reduce dependence on fossil energy and to increase value added of palm oil. With the development of the biodiesel industry, Indonesia's consumption of crude palm oil (CPO) will increase. It is feared that this could lead to an increase in domestic CPO prices. This research was conducted to analyze the impact of developing the biodiesel industry on domestic CPO prices. The data used is secondary data in the form of annual data from 1997-2021. The research analysis used multiple linear regression which is processed with Ordinary Least Square (OLS). The independent variables in this research are international CPO prices, CPO export volumes, fresh fruit bunches (FFB) price and volume of biodiesel production. The real domestic CPO price was significantly affected by international CPO prices, CPO export volume, and FFB prices. Volume of biodiesel production has no significant impact on domestic CPO price.